Coping with stressful life disruptions due to long COVID: A qualitative study - Marina B. Wasilewski; Jaylyn Leighton; Logan Reis; Abirami Vijayakumar; Mahala English; Kris Sanchez; Sander L. Hitzig; Michelle L.A. Nelson; Christine Sheppard; Lawrence Robinson; Rosalie Steinberg; Melody Nguyen; et al. (PLoS ONE, 2025)
Background Long COVID impacts people’s physical health and cognition which immensely affects their psychosocial well-being. A larger study was conducted that explored the psychosocial impacts of Long COVID on individuals and caregivers. This paper focuses on the impact of these stressful disruptions on one’s health and psychosocial well-being, and how individuals cope with them. Methods Utilizing a qualitative descriptive approach, we conducted interviews with 67 participants (52 people with Long COVID (mean age: 50.4) and 15 caregivers (mean age: 50.0)). People with Long COVID and caregivers were recruited from healthcare institutions through care team referrals, patient partners, and health organizations and via social media platforms. A thematic codebook developed through inter-coder agreement processes was used to analyze the data. Findings Three key themes were identified: (1) Disruptions in people with Long COVID and caregivers’ lives are characterized by a deviation from their perceived ‘normalcy’, (2) Disruptions lead to substantial stress, loss and grief (independence, agency, meaning, and purpose), and (3) People with Long COVID and caregivers cope with stressful disruptions by adapting their daily activities. Conclusion Our findings make the case for supportive rehabilitation strategies that address the psychosocial repercussions of Long COVID to help mitigate feelings of loss and grief, thereby increasing individuals’ overall quality of life and well-being.